Hubungan Antara Body Image Dan Komparasi Sosial Dengan Kecemasan Sosial Pada Siswi Smk Putra Bangsa Depok - Fani Akalia; Mia Anita Lestari; Mira Rizki Wijayani (PT. Hasba Edukasi Mandiri, 2025)
The aim of this study is to determine the relationship between Body Image and Social Comparison with Social Anxiety among female students at SMK Putra Bangsa. This research is a multivariate correlation study using data collection techniques in the form of Body Image Scale, Social Comparison Scale, and Social Anxiety Scale. The population in this study consists of individuals aged 15-16 years who are active students of SMK Putra Bangsa in class X. The sample of this study consists of 128 respondents, selected using the Saturated Sampling technique. The Body Image variable scale is the MBSRQ_AS or Multidimensional Body Self Relations Questionnaire Appearance Scale. The Social Comparison Scale is the Upward and Downward Appearance Comparison Scale (UDACS), while the Social Anxiety Scale is the SAS-A scale. The analysis results show that the correlation coefficient of the product moment Pearson between Body Image and social anxiety is r = 0.327, Social Comparison and Social Anxiety is r = 0.388, and the relationship between Body Image and Social Comparison with Social Anxiety among female students at SMK Putra Bangsa has a correlation coefficient (R) of 0.442. It can be concluded that there is a relationship between Body Image and Social Comparison with Social Anxiety among female students at SMK Putra Bangsa.